2001
DOI: 10.1212/wnl.57.6.990
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cerebral white matter abnormalities in older people with gait dysfunction

Abstract: Some older people develop gait and balance dysfunction that is associated with gradual onset of cerebral white matter disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
182
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(214 citation statements)
references
References 27 publications
23
182
7
Order By: Relevance
“…31 We have shown that progression of PV WMH volume is associated with increased gait slowing over time. The relationship between increased rate of WMH burden and worse performance on gait testing over time has been reported, 15,32 although previous studies did not examine the potential differential relationships between subcortical and PV WMH volume change and progressive gait dysfunction. Increased progression of subcortical WMH lesions was associated with increased rate of memory decline, independent of cerebral or hippocampal atrophy.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…31 We have shown that progression of PV WMH volume is associated with increased gait slowing over time. The relationship between increased rate of WMH burden and worse performance on gait testing over time has been reported, 15,32 although previous studies did not examine the potential differential relationships between subcortical and PV WMH volume change and progressive gait dysfunction. Increased progression of subcortical WMH lesions was associated with increased rate of memory decline, independent of cerebral or hippocampal atrophy.…”
Section: Figurementioning
confidence: 99%
“…The question as to whether there is likely to exist a differential effect of total WMH burden on age-related morbidity based on the location within the CNS of white matter change remains unanswered. Longitudinal studies looking at the progression of WMH have been reported [9][10][11][12][13][14][15][16][17][18][19] ; however, differences in methodologies of WMH measurement make comparisons difficult. A poor cor-relation in estimated WMH burden between differing visual rating scales 20 and increased reliability and sensitivity of WMH volumetric measurements 21 make studies using volumetric measures preferable to those that use visual rating scales.…”
mentioning
confidence: 99%
“…shown that, in healthy subjects, the average increase in WMH volume was 1.1cm 3 over four years in one study 41 and 0.1cm 3 over six years in another. 42 However, when subjects with only punctate lesions were excluded from the analysis, those with confluent lesions showed a WMH volume increase of up to 9.3cm 3 over the six years.…”
Section: Progressionmentioning
confidence: 80%
“…Glmnet requires the user to set two parameters related to the penalty: alpha was set at 0.5 to represent an exact mixture of lasso and ridge regression and lambda was determined using k-fold crossvalidation to minimize misclassification error. Fifty-seven brain regions were included as predictors and 3 additional variables (age, total intracranial volume, and log-transformed white matter hypointensity) were included as covariates, based on biological relevance (Whitman et al 2001;Debette and Markus 2010). These covariates were not subjected to the elastic net penalty.…”
Section: Discussionmentioning
confidence: 99%
“…These steps provide quantification of cerebral white matter, gray matter, and subcortical volume. It also provided white matter hypointensity volume and estimated total intracranial volume (to account for difference in head size) which we included as covariates in our analyses (Whitman et al 2001;Debette and Markus 2010). Specifically, estimated total intracranial volume is determined through Freesurfer via atlas scaling factor -a determinant of linear transformation used to align individual structural image to an atlas (Buckner et al 2004).…”
Section: 26mentioning
confidence: 99%